Cross-sectional analysis of deprivation and ideal cardiovascular health in the Paris Prospective Study 3. Issue 23 (27th June 2016) - Empana, J P; Perier, M C; Singh-Manoux, A; Gaye, B; Thomas, F; Prugger, C; Plichart, M; Wiernik, E; Guibout, C; Lemogne, C; Pannier, B; Boutouyrie, P; et al.
Abstract : Aims: We hypothesised that deprivation might represent a barrier to attain an ideal cardiovascular health (CVH) as defined by the American Heart Association (AHA). Methods and results: The baseline data of 8916 participants of the Paris Prospective Study 3, an observational cohort on novel markers for future cardiovascular disease, were used. The AHA 7-item tool includes four health behaviours (smoking, body weight, physical activity and optimal diet) and three biological measures (blood cholesterol, blood glucose and blood pressure). A validated 11-item score of individual material and psychosocial deprivation, the Evaluation de la Précarité et des Inégalités dans les Centres d'Examens de Santé—Evaluation of Deprivation and Inequalities in Health Examination centres (EPICES) score was used. The mean age was 59.5 years (standard deviation 6.2), 61.2% were men and 9.98% had an ideal CVH. In sex-specific multivariable polytomous logistic regression, the odds ratio (OR) for ideal behavioural CVH progressively decreased with quartile of increasing deprivation, from 0.54 (95% CI 0.41 to 0.72) to 0.49 (0.37 to 0.65) in women and from 0.61 (0.50 to 0.76) to 0.57 (0.46 to 0.71) in men. Associations with ideal biological CVH were confined to the most deprived women (OR=0.60; 95% CI 0.37 to 0.99), whereas in men, greater deprivation was related to higher OR of intermediate biological CVH (OR=1.28; 95% CI 1.05 to 1.57 for the third quartile vs the first quartile). Conclusions: Higher material and psychosocial deprivation may represent a barrier to reach an ideal CVH. Trial registration number: NCT00741728.